Charging infrastructure construction from the perspective of new infrastructure - Jing-Lei Yu; Qin Jia; Hua-Qing Hu (Energy Reports, 2021)
In order to predict the demand for airport charging facilities/piles, a demand prediction model was proposed for airports, which includes airside and landside of airports. The airside prediction model was calculated according to air traffic volume and vehicle pile ratio. The landside prediction model was calculated according to the electric vehicle flow and charging probability. Results showed that the number of charging piles in China mainland airports would reach 536000, including 26000 charging piles on the airside and 510000 on the landside in 2035. The relevant policy suggestions from the aspects of investment, operation management, and technical standards were put forward and the “new infrastructure” technology was suggested to be applied in airport’s intelligent charging facility network building.